2017
DOI: 10.1080/01616412.2017.1365423
|View full text |Cite
|
Sign up to set email alerts
|

The vascularization pattern of acellular nerve allografts after nerve repair in Sprague-Dawley rats

Abstract: Both the autologous nerve and ANAs rely on the permeation of tissue fluids to supply nutrients during the early stage, and microvessel growth mainly starts at both ends of the graft and enters the graft along the long axis. Compared to ANAs, the growth speed of revascularization in autologous nerve grafts was faster, leading to a better outcome in the autologous nerve group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 20 publications
3
23
0
Order By: Relevance
“…There are three main decellularization protocols for the creation of a functional graft: the one described by Sondell et al (1998) and Hudson et al (2004) , and the combined Hudson protocol added with chondroitinase ABC by Krekoski et al (2001) . SP was used in 33% of the studies ( Jia et al, 2012 , 2017 ; Wang et al, 2012 ; Zhang et al, 2014 ; Zheng et al, 2014 ; Zhou et al, 2014 ; Zhu and Weihua, 2014 ; Huang et al, 2015 ; Garcia-Pérez et al, 2017 ; Zhu et al, 2015 , 2017 ); HP was used in 24% ( Saheb-Al-Zamani et al, 2013 ; Gao et al, 2014a ; Hoben et al, 2015 ; Marquardt et al, 2015 ; Kim et al, 2016 ; Tajdaran et al, 2016 ; Yan et al, 2016 ; Cai et al, 2017 ), and a combined HP was used in 12% ( Whitlock et al, 2009 ; Vasudevan et al, 2014 ; Wood et al, 2014 ; Jiang et al, 2016 ). Other studies (6%) used a FTP with or without the addition of chondroitinase ABC as introduced by Krekoski et al (2001 ; Godinho et al, 2013 ; Wang H. et al, 2016 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There are three main decellularization protocols for the creation of a functional graft: the one described by Sondell et al (1998) and Hudson et al (2004) , and the combined Hudson protocol added with chondroitinase ABC by Krekoski et al (2001) . SP was used in 33% of the studies ( Jia et al, 2012 , 2017 ; Wang et al, 2012 ; Zhang et al, 2014 ; Zheng et al, 2014 ; Zhou et al, 2014 ; Zhu and Weihua, 2014 ; Huang et al, 2015 ; Garcia-Pérez et al, 2017 ; Zhu et al, 2015 , 2017 ); HP was used in 24% ( Saheb-Al-Zamani et al, 2013 ; Gao et al, 2014a ; Hoben et al, 2015 ; Marquardt et al, 2015 ; Kim et al, 2016 ; Tajdaran et al, 2016 ; Yan et al, 2016 ; Cai et al, 2017 ), and a combined HP was used in 12% ( Whitlock et al, 2009 ; Vasudevan et al, 2014 ; Wood et al, 2014 ; Jiang et al, 2016 ). Other studies (6%) used a FTP with or without the addition of chondroitinase ABC as introduced by Krekoski et al (2001 ; Godinho et al, 2013 ; Wang H. et al, 2016 ).…”
Section: Resultsmentioning
confidence: 99%
“…Given the importance of this issue, and in order to better understand the process of vascularization in decellularized grafts, we analyzed two studies. Zhu et al (2017) evaluated patterns of microangiogenesis in decellularized grafts, while Farber et al (2016) completed the study by Saheb-Al-Zamani et al (2013) investigating the difference in vascularization between long auto/isografts and decellularized grafts. Zhu et al (2017) studied short grafts (10 mm in length) and demonstrated that nutrient supply relies on fluid permeation from the surrounding tissues during the early stages after the graft procedure.…”
Section: Resultsmentioning
confidence: 99%
“…A proliferative phase follows, in which the number of inflammatory cells decreases while myofibroblast and endothelial cells increase in correspondence to revascularization. Multiple studies have found almost complete revascularization after 7 days in subcutaneous models, 5,9,[11][12][13] but longer in less vascularized tissues such as breast reconstruction models and tracheal scaffolds. 10,14 Eppley found that subcutaneous revascularization occurred from both surfaces regardless of the orientation of the graft's original basement membrane and that revascularization takes longer to complete when multilayered grafts are used.…”
Section: Discussionmentioning
confidence: 99%
“…Similar procedures were used in synthesis of PDAPEI polymers as described in our previous work [18,19]. In brief, 2 mmol PDA dissolving in 20 mL DMF were dropwise added into 20 mL DMF containing 1 mmol PEI (1.8 kDa) with vigorous stirring.…”
Section: Synthesis Of Pdapei Polymersmentioning
confidence: 99%
“…With the growth and regeneration of peripheral nerve, metabolic demands are urgently increasing, in which more oxygen and nutrients are needed for the supply, and more waste products need to be removed. In this case, enough blood vessels are of much essence, to exchange nutrients and waste products with outer environment and maintain the viability of new regenerative nerves [16][17][18][19]. Besides that, impressive comparisons in distribution pattern between the nervous and vascular network were made in several studies [12,20,21].…”
Section: Introductionmentioning
confidence: 99%